2023
DOI: 10.37520/fi.2023.004
|View full text |Cite
|
Sign up to set email alerts
|

Diverse fruits and seeds of the mid-Eocene Kishenehn Formation, northwestern Montana, USA, and their implications for biogeography

MacKenzie A. Smith,
Dale E. Greenwalt,
Steven R. Manchester

Abstract: Lacustrine shales of the Kishenehn Formation of northwestern Montana provide an important window to the local mid-Eocene (Lutetian) ecosystem including evidence from insects, molluscs, vertebrates and plants. However, little has been published on the macrofossils flora, which includes abundant compressed fruits and seeds as well as foliage. Here we provide a preliminary survey, with particular attention to reproductive remains from the Middle Fork Region. Identified families include Equisetaceae, Cupressaceae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 124 publications
(251 reference statements)
0
0
0
Order By: Relevance
“…(Penhallow 1908) and illustrated as a "burr" from Republic by Pigg and Wehr (2002). Disseminules of this type have been designated as Pteroheterochrosperma horseflyensis (Smith et al 2023). Another interesting disseminule is characterized by a hard central body with arched longitudinal ridges and a punctate surface (Textfig.…”
Section: "Dicots"mentioning
confidence: 99%
See 2 more Smart Citations
“…(Penhallow 1908) and illustrated as a "burr" from Republic by Pigg and Wehr (2002). Disseminules of this type have been designated as Pteroheterochrosperma horseflyensis (Smith et al 2023). Another interesting disseminule is characterized by a hard central body with arched longitudinal ridges and a punctate surface (Textfig.…”
Section: "Dicots"mentioning
confidence: 99%
“…These include a small seed (Text-fig. 10f) recently described as Pteroheterochrosperma horseflyensis (Smith et al 2023) that is commonly found at Republic (Pigg and Wehr 2001) and a flower with a distinctive papillate surface that may be assignable to Apiaceae (Textfig. 10g, k).…”
Section: Observations On the Horsefly Floramentioning
confidence: 99%
See 1 more Smart Citation